Local electron heating in the Io plasma torus associated with Io from HISAKI satellite observation. Issue 12 (8th December 2015) - Tsuchiya, Fuminori; Kagitani, Masato; Yoshioka, Kazuo; Kimura, Tomoki; Murakami, Go; Yamazaki, Atsushi; Nozawa, Hiromasa; Kasaba, Yasumasa; Sakanoi, Takeshi; Uemizu, Kazunori; Yoshikawa, Ichiro
Abstract: Io ‐correlated brightness change in the Io plasma torus (IPT) was discovered by the Voyager spacecraft, showing evidence of local electron heating around Io . However, its detailed properties and the cause of electron heating are still open issues. The extreme ultraviolet spectrograph on board the HISAKI satellite continuously observed the IPT from the end of December 2013 to the middle of January 2014. The variation in the IPT brightness showed that clear periodicity associated with Io 's orbital period (42 h) and that the bright region was located downstream of Io . The amplitude of the periodic variation was larger at short wavelengths than at long wavelengths. From spectral analyses, we found that Io ‐correlated brightening is caused by the increase in the hot electron population in the region downstream of Io . We also found that the brightness depends on the system III longitude and found primary and secondary peaks in the longitude ranges of 100–130° and 250–340°, respectively. Io 's orbit crosses the center of the IPT around these longitudes. This longitude dependence suggests that the electron heating process is related to the plasma density around Io . The total radiated power from the IPT in January 2014 was estimated to be 1.4 TW in the wavelength range from 60 to 145 nm. The Io ‐correlated component produced 10% of this total radiated power. The interaction between Io and the IPT continuously produces a large amount of energy around Io, and 140 GW of that energy is immediately converted to hot electron production in the IPT. Key Points: Hot electron population downstream of Io enhances brightness in Io torus Hot electron heating is related with the plasma density at the position of Io One‐hundred‐forty gigawatts of power generated around Io is immediately converted to hot electron production